Downward wage rigidity in Europe: A new flexible parametric approach and empirical results - Andreas Behr; Ulrich Pötter (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2005)
We suggest a new parametric approach to estimate the extent of downward nominal wage rigidity in ten European countries between 1994 and 2001. The data base used throughout is the User Data Base (UDB) of the European Community Household Panel (ECHP). The proposed approach is based on the very flexible generalized hyperbolic distribution which allows to model wage change distributions characterized by thick tales, skewness and leptokurtosis. Significant downward nominal wage rigidity is found in all countries under analysis, but the extent varies considerably across countries. Yearly estimates reveal increasing rigidity in Italy, Greece and Portugal, while rigidity is declining in Denmark and Belgium. The results imply that the costs of price stability differ substantially across Europe.
Keywords: E24; J30; C51; 330